KLASTERISASI TINGKAT PENJUALAN OBAT PADA APOTEK JAKA WIJAYA DENGAN MENGGUNAKAN METODE K-MEANS - deni andria hidayanti; fitri kurnia; rahmawati rahmawati (LPPM STMIK Royal Kisaran, 2024)
Abstrak: A pharmacy is a health service facility to help improve the health of the community, a pharmacy is also a place for professional pharmacists to practice their work. To determine the amount of stock inventory, Jaka Wijaya Pharmacy requires a clusterization of sales stock data. The method that can be used is the K-Means algorithm. This algorithm is based on a simple idea. K-Means is a distance-based clustering method that divides data into a number of clusters and this algorithm only works on numeric attributes. The data processed in this research is a sample taken from the Jaka Wijaya Pharmacy data in 2022. The Jaka Wijaya Pharmacy dataset consists of the attributes No, Drug Item, Type, Packaging, Initial Stock, Cost Price, Unit Conversion, Selling Price, Number of Transactions, Ending Stock, Shelf, Warehouse-Office Codes. With the K-Means Clustering method, it is possible to group drug sales data with stock that is not selling well as cluster 0, stock that is selling well as cluster 1, and stock that is selling very well as cluster 2. The sample data to be tested consists of 170 data from the Jaka Wijaya Pharmacy. Where the cluster results show that there are several results, namely cluster 0 totaling 102, cluster 1 totaling 34, and cluster 2 totaling 34 decisions, where the decisions include very in demand, in demand, not in demand.Keywords: Data Mining; Jaka Wijaya Pharmacy; K-means ClusterAbstrak: Apotek merupakan sarana pelayanan kesehatan untuk membantu meningkatkan kesehatan bagi masyarakat, apotek juga sebagai tempat praktik tenaga profesi apoteker dalam melakukan pekerjaan. Untuk menentukan jumlah persediaan stok, Apotek Jaka Wijaya membutuhkan suatu clusterisasi data stok penjualan. Metode yang dapat digunakan yaitu algoritma K-Means. Algoritma ini didasarkan pada ide sederhana. K-Means adalah metode Clustering berbasis jarak yang membagi data ke dalam sejumlah cluster dan algoritma ini hanya bekerja pada atribut numeric. Data yang diolah dalam penelitian ini merupakan sampel yang diambil dari data Apotek Jaka Wijaya pada tahun 2022. Dataset Apotek Jaka Wijaya terdiri dari atribut No, Item Obat, Jenis, Kemasan, Stok Awal, Harga Pokok, Konversi Satuan, Harga Jual, Jumlah Transaksi, Stok Akhir, Rak, Kode Gudang-Kantor. Dengan metode K-Means Clustering maka dapat mengelompokkan data penjualan obat dengan stok kurang laris sebagai cluster 0, stok laris sebagai cluster 1, dan stok sangat laris sebagai cluster 2. Data sampel yang akan diuji terdiri dari 170 data dari Apotek Jaka Wijaya. Yang dimana hasil cluster menunjukkan terdapat beberapa hasil yaitu cluster 0 berjumlah 102, cluster 1 berjumlah 34, dan cluster 2 berjumlah 34 keputusan yang dimana keputusan itu meliputi sangat laris, laris, kurang laris. Kata kunci: Apotek Jaka Wijaya; Data Mining; K-means Cluster